Molecular characterisation of ASXL1-mutant clonal haematopoiesis - Groom, AJ (2024)
Adult stem cells accumulate somatic mutations throughout life as a result of failure to repair DNA damage. If a somatic mutation confers a fitness advantage upon the stem cell, the resulting clone can expand to be over-represented in that tissue. In the haematopoietic system, this process is known as clonal haematopoiesis (CH). Whilst CH is a common condition amongst older healthy individuals, it has been associated with a greater risk of developing leukaemia. One of the genes that is most frequently found mutated in CH and myeloid malignancies is ASXL1- a regulator of histone modification distribution. Mutations in ASXL1 are associated with poor prognosis of blood cancers, and are likely to be acquired years before the onset of disease. Thus far, the mechanisms by which ASXL1 confers a clonal expansion upon haematopoietic stem and progenitor cells are poorly understood. Identification of these mechanisms could reveal novel therapeutic strategies for blood cancer.